Impact of Garlic-infused Salt Supplement on Fly Abundance, Salt Intake, and Defensive Behaviors in Grazing Beef Cows - Durunna, Obioha; Lardner, Herbert (Sustainable agriculture research, 2020)
This study evaluated the efficacy of free-choice feeding of garlic-infused salt as an alternative pest-fly control strategy in grazing beef cows. This on-farm study is relevant because pest-fly abundance during the summer can impact performance and may cause welfare concerns on beef cattle operations. Over two consecutive summers, three groups of grazing cows received either a trace-mineral salt (TMS) supplement or a TMS infused with garlic powder (GPTMS). The study assessed the treatment effects on fly abundance, defensive behavior, and salt consumption for each group. All cows grazed similar forage species. Fly abundance and defensive behaviors were evaluated in each group using digital imagery. The results showed no difference (P = 0.34) in monthly salt consumption among groups. There were differences (P < 0.0004) in fly abundance among groups where one GPTMS group had at least 47% fewer flies and 41% fewer defensive behaviors than the TMS groups. On the other hand, another group that received GPTMS in the second year indicated a trend (P = 0.07) in fly abundance from its previous outcomes when the group received the TMS in the first year. These differing results for fly abundance and defensive behavior in the groups that received the GPTMS suggest that the efficacy of this feeding strategy in cattle may be affected by differences in genetic or environmental factors or both. We recommended that future studies consider genomic breed compositions before assigning subjects to different groups. Additional studies are required to investigate the variation in individual supplement intake between treatment groups and whether infusing mineral supplements with garlic powder is associated with similar outcomes as salt.